2006
DOI: 10.2175/193864706783763002
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Cyanide Generation in Chlorinated Wastewater Effluent Matrix

Abstract: False positives for cyanide analysis in wastewaters have been reported. We examined the effects of storage time at high pH and of pH adjustments on the cyanide levels. Cyanide levels changed within the holding time allowed by Standard Methods. We also studied the difference in cyanide levels using two disinfection conditions --breakpoint chlorination and chloramination. Glycine was used as the precursor to study the cyanide formation pathways. Under breakpoint chlorination conditions, cyanide formation is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The results support the conclusions reported in the literature (Khoury et al, 2008;Pandit et al, 2006;Zheng, Dzombak, Luthy, Kavanaugh, and Deeb, 2004). However, in the former study, all samples were preserved and comparisons of final effluent to prior stages and influent at the WWTF were made.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results support the conclusions reported in the literature (Khoury et al, 2008;Pandit et al, 2006;Zheng, Dzombak, Luthy, Kavanaugh, and Deeb, 2004). However, in the former study, all samples were preserved and comparisons of final effluent to prior stages and influent at the WWTF were made.…”
Section: Resultssupporting
confidence: 90%
“…It was then showed that the analytical preservation step may be responsible for much of the increases observed in chlorinated/ dechlorinated water samples and that different mechanisms occur with breakthrough chlorination and chloramination (Khoury et al, 2008;Pandit et al, 2006). Total cyanide analysis was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Though more complex than drinking water, cyanide formation has been studied more extensively in domestic and industrial wastewater . Several wastewater studies have shown the cyanide can form during preservation and storage . Weinberg, et al , concluded that “an unknown, reactive, carbon-containing compound reacts with chlorine to form a cyanide precursor compound.…”
Section: Resultsmentioning
confidence: 99%
“…In an extensive study of hundreds of samples collected at four California wastewater treatment plants , , virtually all of the samples tested without pH preservation were nondetect for CN − at 5 µg/L, regardless of the dechlorinating agent used. But when these same samples were preserved by being adjusted to pH >12, cyanide tended to be detected.…”
Section: Resultsmentioning
confidence: 99%
“…In 1994 an EPA consultant stated that the approved total cyanide methods in wastewater at that time were “dysfunctional” (Goldberg, 1994). Since then a number of researchers have examined the performance of various analytical methods for various forms of cyanide and the impact of sample preservation and pretreatments for positive and negative interferences (Milosavljevic, 1995; Carr, 1997; Weinberg and Cook, 2002; Zheng, 2003; Deeb, 2003; Gulino, 2004; Zheng, 2004a‐d; Zheng, 2004; Weinberg et al, 2005; Khoury et al, 2005; Pandit et al, 2006; Khoury et al, 2008; Stanley and Antonio, 2012). For example, Stanley and Antonio (2012) showed that preservation of wastewater samples with sodium hydroxide caused an “artificial increase” in cyanide levels compared to unpreserved samples and that this increase was not a matrix interference.…”
Section: Introductionmentioning
confidence: 99%